MENDAMBAKAN PARADIGMA KESETARAAN DALAM PERNIKAHAN (TELAAH KRITIS TERHADAP KITAB UQU>D AL-LUJJAIN) - Fatah, Ahmad (LP2M IAIN kUDUS, 2014)
CRAVING THE PARADIGM EQUALITY IN MARRIAGE (CRITICAL ANALYSIS OF Uqu>d al-Lujjain BOOK).Based on simple study to Uqu>d al-Lujjain book, it is known that in the Uqu>d al-Lujjain book there are a variety of texts that emphasizes the superiority of men in the marital relationship. It is much influenced by socio-cultural settings at that time, besides the hadith references which aren’t all saheeh and hasan, but there is a weak. The discussion in this research reveal the fundamental problem in understanding the rights and responsibilities of husband and wife who can be classified into four things, namely the problem of husband and wife relationship in tradition, the problem of space in the marital relationship, situation and condition problems, as well as the problem in understanding the text of al-Qur`an and Hadith. Thus, in this paper the authors offer is continued criticism conceptually contained in Uqu>d al Lujjain with criticism of reality in household which is particularly problematic in a relationship of husband and wife.keywords: Equality, Marriage, Family.Berdasarkan kajian yang sederhana terhadap kitab Uqu>d al-Lujjain, dapat diketahui bahwa dalam kitab Uqu>d al-Lujjain terdapat berbagai teks yang mengedepankan superioritas laki-laki dalam hubungan suami istri. Hal ini banyak diwarnai oleh setting sosial budaya pada saat itu, disamping rujukan hadis-hadis yang tidak semuanya shahih dan hasan, tetapi ada yang dhaif. Bahasan dalam peneltian ini mengungkap problem yang mendasar dalam memahami hak dan kewajiban suami istri yang dapat diklsifikasikan menjadi empat hal, yaitu problem relasi suami istri dalam tradisi, problem ruang gerak dalam hubungan suami istri, problem situasi dan kondisi, serta problem pemahaman terhadap teks al Qur`an maupun Hadis. Dengan demikian, dalam penelitian ini yang penulis tawarkan adalah melanjutkan kritik secara konseptual yang terdapat dalam Uqu>d al- Lujjain dengan kritik terhadap realitas dalam rumah tangga yang sangat problematik dalam menjalin hubungan suami istri.kata kunci: Kesetaraan, Pernikahan, Keluarga.